Under the skin : Biological Transformations in Contemporary Art. - Heidt Heller, Renate; Brockhaus, Christoph; Bartens, Werner; Dinkla, Söke; Lehmbruckmuseum, Duisburg (Ostfildern-Ruit : Hatje Cantz, 2001)
Chapman, Jake & Dinos ; Clarke, Kevin ; Feingold, Ken ; Florschuetz, Thomas ; Fuchs, Harald ; Grünfeld, Thomas ; Horlitz, Andreas ; Kac, Eduardo ; Kulik, Oleg ; Lewandowsky, Via ; Sun, Lim Young ; Oursler, Tony ; et al.
Lehmbruckmuseum, Duisburg, 6. Mai - 17. Juni 2001
kunstcatalogus